Comprehensive Studies on the Hydrothermal Strategy for the Synthesis of Na3(VO1−xPO4)2F1+2x (0 ≤ x ≤ 1) and their Na‐Storage Performance. Issue 4 (11th June 2018) - Qi, Yuruo; Zhao, Junmei; Yang, Chao; Liu, Huizhou; Hu, Yong‐Sheng
Abstract: Sodium vanadium fluorophosphate, Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1), is proved to be a series of very promising cathode materials for Na‐ion batteries, owing to the high operating voltage and structural stability. However, the selective preparation of phase‐pure Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1) with outstanding electrochemical performance still remains a big challenge. Moreover, there are lots of discrepancies concerning the Na‐storage properties, including a diversity of voltage profiles and capacities reported, based on the variety of synthetic methods. Herein, a comprehensive investigation is conducted about the fabrication of phase‐pure Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1) by employing different starting materials and corresponding synthetic conditions, based on a facile low‐temperature hydrothermal strategy. Results show that the pH in the reaction system may be of vital importance for the successful preparation of Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1) with special microarchitecture. Furthermore, it is found that NaH2 PO4 ·2H2 O is the most appropriate phosphorus source, while VCl3, VOSO4 · x H2 O, and NH4 VO3 are the best choices of vanadium sources to prepare Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1) with superior Na‐storage performance. This is the first time that the underlying correlations between the starting materials and the Na‐storage performance, are investigated and further that guidance for the selective synthesis of phase‐pure Na3 (VO1− x PO4 )2 F1+2 x (0 ≤ x ≤ 1) with superior performance is provided. Abstract : The pH value is of vital importance for the successful preparation and micro‐texture of sodium vanadium fluorophosphate. Moreover, its electrochemical performance is closely related to the pH values. The discharge capacity significantly decreases following the sequence of H3 PO4, NaH2 PO4 2H2 O, Na2 HPO4 12H2 O, Na3 PO4 . Samples obtained using NaH2 PO4 2H2 O show excellent cycling performance and rate capability for any vanadium sources.